PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH DAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA - Samsidar Samsidar (UNIB Press, 2020)
This study aims to (1) describe the application of problem based learning, improve students 'scientific thinking skills (2) improve students' explanatory text writing skills (3) the effectiveness of applying problem based leaning to improve learning outcomes. This study uses the Classroom Action research method and the quasi-experimental method, the data collection method in this study uses the observation sheet to measure the ability of teachers to apply problem-based leaming models, measure scientific thinking skills and increase students' writing skills, the data are processed qualitatively and quantitatively by the average test evenly to see the effectiveness of the dependent sample t-test and that the application of the problem based learning model increases the ability of scientific thinking to improve student writing skills and effectively improve learning outcomes in Indonesian subjects. Keywords Problem Based Leaning. Imial Thinking, Exploratory Text Explanations